Prosedur dan Penyelesaian Dispensasi Nikah Di bawah Umur Di Pengadilan Agama - Muhajir, Muhajir (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
Marriage is a momentum that is very important for the journey of human life. Besides bringing the bride and groom to a different realm, marriage will also automatically change the status of both. After the marriage, both parties will receive heavy burdens and responsibilities according to their respective nature. Responsibilities and burdens are not something that is easily implemented, so they must assume these responsibilities and carry them out. Marriage must be based on the agreement of the bride and groom. If the prospective husband has not reached the age of 19 years and the prospective wife has not yet reached the age of 16 want to get married must get a marriage dispensation from the Religious Court. Requests for marriage dispensation for those who have not yet reached the age of 19 years and 16 years, the prospective husband and wife are submitted by both male and female parents to the Religious Courts in the area of ​​their residence. The Religious Court, after examining the trial and believes that there are things that are possible to provide the dispensation, the Religious Court provides marriage dispensation with a determination.